Compensatory Changes in Ground Reaction Forces in Small and Large Breed Dogs with Unilateral Hindlimb Lameness in Comparison to Healthy Dogs - Wagmeister, Patrick; Steigmeier-Raith, Stephanie; Reese, Sven; Meyer-Lindenberg, Andrea (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective The aim of this study was to investigate whether small- to medium-sized dogs with a naturally occurring unilateral hindlimb lameness show the same compensatory changes in ground reaction forces as large-breed dogs and how the changes are displayed compared with healthy small- to medium-sized dogs.Study Design Small- to medium-sized dogs (n = 15) and large-breed dogs (n = 16) with unilateral rupture of the cranial cruciate ligament were examined. The kinetic parameters peak vertical force and vertical impulse of the two groups were compared with each other and compared with healthy Beagles (n = 15) and with healthy Labrador Retrievers (n = 17), respectively.Results The healthy Beagle group showed a significantly higher weight loading on the forelimbs compared with the healthy Labrador group. The affected groups in comparison with the corresponding healthy groups showed a higher load on the non-affected body half and a significant lower weight bearing on the affected limb. Comparing the two affected groups, no significant difference could be found.Conclusion Despite a substantially different initial situation regarding weight distribution of the examined small- to medium-sized dogs and large dogs, a unilateral hindlimb lameness leads to the same compensatory changes (cranial and lateral shift of the body mass centre).
Keywords: kinetic; computerized gait analysis; force distribution; dog; treadmill